2004
DOI: 10.1177/1420326x04047657
|View full text |Cite
|
Sign up to set email alerts
|

Coalinga Chrysotile: A Short Fibre, Amphibole Free, Chrysotile: Part V - Lack of Amphibole Asbestos Contamination

Abstract: Exposure to asbestos in the indoor built environment has been a concern for many years. The most common exposures in that setting are to short ultra-thin, naturally defibrillated form of fibrous asbestiform chrysotile and possibly trace amounts of short, non-asbestiform amphibole. Coalinga chrysotile is a short fibre mineral that was mined from a large ore body in California. It has been investigated in considerable detail since, although it is widely believed to be amphibole free, evidence for this has not hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Ilgren (2004) summarized these results stating that “Only very rarely have non-asbestiform ‘non-friable’ amphibole (so-called cleavage fragment) minerals been found in the New Idria serpentine body but away from the ore zone”.…”
Section: Use and Exposures In The Past And Todaymentioning
confidence: 99%
“…Ilgren (2004) summarized these results stating that “Only very rarely have non-asbestiform ‘non-friable’ amphibole (so-called cleavage fragment) minerals been found in the New Idria serpentine body but away from the ore zone”.…”
Section: Use and Exposures In The Past And Todaymentioning
confidence: 99%
“…Bernstein et al [19] found clusters [2,12]. 28 Indoor Built Environ 2008;17:27- 41 Ilgren in air samples taken from their animal exposure chambers and the King City Mill. They said these were dramatically different from Canadian fibers [20] and ''composed of multiple fibrils of shorter length''.…”
Section: Qualitative Support For the Nonrespirability Of Airborne Coamentioning
confidence: 99%
“…''A series of electron micrographs of defibrillated Canadian Grade 7R and defibrillated New Idria flake were prepared and the external diameters of a statistical sampling of the fibrils appearing on each photographic plate were measured using an optical microscope with a filar eyepiece. Histograms of the distribution of fibril diameters determined in this way are shown in ( Figure 5; also [28]). The Canadian specimen had a larger average diameter and a greater variation in diameter than the New Idria material.…”
Section: Width Distributions Of Coalinga Chrysotile Fibers In Aqueousmentioning
confidence: 99%
See 1 more Smart Citation
“…This muddies the waters somewhat. One problem is that some amphibole minerals are found in close association with chrysotile, although this is not the case with the chrysotile in question [3]. Also, the fibrous amphiboles and chrysotile were, in the past, lumped together for commercial reasons and all given the name ''asbestos''.…”
mentioning
confidence: 99%